Effects of oligosaccharides on the markers of glycemic control: a systematic review and meta-analysis of randomized controlled trials. Issue 17 (10th August 2022) - An, Ran; Zong, Aizhen; Chen, Shanbin; Xu, Rui; Zhang, Ruixin; Jiang, Wen; Liu, Lina; Du, Fangling; Zhang, Hongyan; Xu, Tongcheng
Abstract : This study is by far the most extensive systematic review to evaluate the role of oligosaccharides on markers of glycemic control. Meta-analysis revealed that oligosaccharide interventions can exert beneficial effects on FBG, FBI, HbA1c and HOMA-IR. Abstract : Objective : To investigate the effect of oligosaccharides on the markers of glycemic control, including fasting blood glucose (FBG), fasting blood insulin (FBI), glycated hemoglobin (HbA1c ), homeostasis model assessment of insulin resistance (HOMA-IR), and quantitative insulin sensitivity index (QUICKI). Methods : PubMed, Embase, and the Cochrane Library databases were systematically searched to find randomized controlled trials (RCTs) on the effect of oligosaccharide intervention on FBG, FBI, HbA1c, HOMA-IR, and QUICKI up to 7 June 2021. Data were pooled using weighted mean difference (WMD) and 95% confidence intervals (95% CI), with a p -value ≤0.05 indicating statistical significance. Risk of bias was assessed with the Cochrane tool and the quality of the literature with the new Jadad scale. Results : A total of 46 randomized controlled trials were included. Oligosaccharides significantly reduced FBG (WMD: −0.295 mmol L −1 ; 95% CI: −0.396 to −0.193; p < 0.001; I 2 = 90.9%; 46 trials; 2412 participants), FBI (WMD: −0.559 pmol L −1 ; 95% CI: −0.939 to −0.178; p < 0.01; I 2 = 99.1%; 29 trials; 1462 participants), HbA1c (WMD: −0.365; 95% CI: −0.725 to −0.005; p < 0.05; I 2 = 86.6%; 11 trials; 661 participants), and HOMA-IR (WMD: −0.793; 95% CI: −1.106 to −0.480; p < 0.001; I 2 = 96.1%; 24 trials; 1382 participants). Oligosaccharides were more beneficial for the participants with obesity or diabetes than for healthy participants. Multiple interventions per day consolidated the effectiveness of oligosaccharides. Regardless of the processing manner (starch-modified or naturally extracted) of the oligosaccharides, their intervention was overall beneficial for the patients with diabetes. Conclusions : This study is by far the most extensive systematic review to evaluate the role of oligosaccharides on the markers of glycemic control. Oligosaccharide interventions can exert beneficial effects on FBG, FBI, HbA1c, and HOMA-IR.